Engineering Multi-Agent Systems First International Workshop, EMAS 2013, St. Paul, MN, USA, May 6-7, 2013, Revised Selected Papers - Cossentino, Massimo.; Cossentino, Massimo.; El Fallah Seghrouchni, Amal.; El Fallah Seghrouchni, Amal.; Winikoff, Michael.; Winikoff, Michael. (Lecture Notes in Artificial Intelligence ;, 2013)
This book constitutes the refereed proceedings of the First International Workshop on Engineering Multi-Agent Systems, EMAS 2013, held in St. Paul, MN,  USA, in May 2013. The 19 full papers  were carefully reviewed and selected from 30 submissions. The focus of the papers is on following topics: agent-oriented software engineering, declarative agent languages and technologies, and programming multi-agent systems.